Work Motivation That Affects the Loyalty of Personnel in Pathumthani Provincial Administrative Organization, Thailand - Nopgate, Suthin; Rattanaphumpinyo, Somchai; Kalyanamith, Rachaporn; Thepsuthin, Anongwan; Luckanapichonchas, Tassanee (Asian Administration and Management Review, 2022)
The objectives of this research were to: 1) explore the loyalty of personnel; 2) explore the motivation that affect the loyalty of personnel; 3) explore work environment that affect the loyalty of personnel; 4) compare the loyalty of personnel divided by personal characteristics. The study was conducted in participants comprises of civil servants, hiring employees, mission employees, and general employee of Pathumthani Provincial Administration Organization, Thailand. This study is survey research. The samples included in this research were based on simple random sampling techniques with a total number of 215 personnel. Research result found that: The overall personnel opinions towards the motivation that affect the loyalty of personnel was at a high level. The overall personnel opinions towards work environment that affect the loyalty of personnel was at a high level. The level of the personnel loyalty towards Pathumthani Provincial Administrative Organization in overall picture and each aspect were all at high level. The difference in individual characteristics including age, education, type of personnel and work experiences resulting in differences of the level of the loyalty towards Pathumthani Provincial Administrative Organization. Pearson Correlation Coefficient analysis found that the overall motivation and work environment had relationship with Pathumthani Provincial Administrative Organization at a very high level in a positive side.